Sensory and chemical characteristics of nori from Indonesian seaweed added with breadfruit leaf extract and grass jelly - Ratna Sari Listyaningrum; Iip Syarip Hidayatulloh (AGROINTEK, 2024)
Nori is an authentic Japanese food made from Porphyra seaweed. However, Porphyra is difficult to cultivate in Indonesia because it generally grows in subtropical areas. The demand for nori continues to increase with the development of Japanese, Korean, and Chinese fast-food restaurants in Indonesia. Therefore, it is necessary to make nori using seaweed easily cultivated in Indonesia, namely Eucheuma cottonii and Ulva lactuca. This research aimed to study the sensory and chemical characteristics of nori from Indonesian seaweed added with breadfruit leaf extract and grass jelly. Dried Eucheuma cottonii was obtained from LIPI Oceanography, while dried Ulva lactuca was obtained from waters in Sidoarjo. Dried breadfruit leaf used in this study were obtained from processing fresh breadfruit leaf from the yards of residents of the Babakan Penghulu Village, Cinambo District. Green grass jelly leaf were obtained from Andir. Three nori formulas were made, namely the addition of breadfruit leaf extract (200 ml), a combination of breadfruit leaf and grass jelly (100:100 ml), and the addition of grass jelly (200 ml). The sensory test is carried out using the hedonic test method with 30 untrained panelists. Panellists were asked for their responses regarding color, taste, texture, aroma, and total acceptance on a scale of 1-5, from very dislike to very like. Chemical testing includes water, ash, protein, fat, crude fiber, and antioxidant activity. The results show that the best formula is the one with the addition of breadfruit leaf extract, which gave an overall acceptance score of 3.37, water content of 5.26%, ash content of 2.41 %, fat content of 2.06%, protein content of 22.24%, starch content of 59.97%, and crude fiber of 6.65%, and antioxidant activity of 702.75 ppm. Nori using local Indonesian seaweed with the addition of breadfruit leaf extract can be an alternative to commercial nori.